The urine bag used in pneumothorax - Kuan, Yeh Chunn; How, Soon Hin; Yudisthra, G.; Ng, Teck Han; Abdul Rani, Mohammed Fauzi; Sapari, Satwi (Malaysian Medical Association, 2008)
Pneumothorax is the presence of air in the pleural cavity. It can be classified into spontaneous, traumatic or iatrogenic. The majority of pneumothorax cases are spontaneous, which can be further classified into primary spontaneous pneumothorax (PSP) or secondary spontaneous pneumothorax (SSP), defined by the absence or presence of obvious underlying lung disease respectively. The treatment of spontaneous pneumothorax includes simple aspiration, intercostal tube drainage or surgical intervention. When intercostal tube drainage is used, it is usually attached to an underwater-seal system. Mobile chest drains, such as the Heimlich valve, replace the underwater-seal and allow outpatient management of spontaneous pneumothoraces. The Heimlich valve however, is costly and not readily available in many local hospitals. Cheaper and easily obtainable alternatives which are also safe are being sought. This is a case report describing the use of the urine bag in the management of a patient with spontaneous pneumothrax.